Ethnography of Communication in Improving Social Interaction of Children with Special Needs : Etnografi Komunikasi dalam Meningkatkan Interaksi Sosial Anak Berkebutuhan Khusus - Rofi’atin; Sufyanto (Indonesian Journal of Innovation Studies, 2023)
The purpose of this study is to describe communicative events, communicative actions, communicative situations between teachers and students with autism in interacting with the school environment at SLB Aisyiah Krian. The research method used in this research is using qualitative research with an ethnographic communication study approach. The results of the study explain that the Ethnography of Communication in Improving Social Interaction of Children with Special Needs "Teachers and Students with Autism SLB Aisyiah Krian" is to show that in the ethnography of communication communication activities are part of the activities of autistic students while learning at school, which can be seen from several components, namely communicative events seen through the word SPEAKING, communicative actions that are identical to the use of non-verbal communication, and communicative situations, namely the location will be considered the same when autistic students interact with the teacher even though the location changes